Presidential Decree-Law No. 142/2014 On Amending Some Provision of the Traffic Law Promulgated by Law No. 66/1973 = قرار رئيس جمهورية مصر العربية بالقانون رقم 142 لسنة 2014 بتعديل بعض أحكام قانون المرور الصادر بالقانون رقم 66 لسنة 1973 / presidency - Egypt. presidency (2025)
Presidential Decree-Law No. 142 of the year 2014 On Amending Some Provision of the Traffic Law Promulgated by Law No. 66 of the year 1973 قرار رئيس جمهورية مصر العربية بالقانون رقم 142 لسنة 2014 بتعديل بعض أحكام قانون المرور الصادر بالقانون رقم 66 لسنة 1973